2018
DOI: 10.1093/infdis/jiy176
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Resistance Dynamics in Patients With Virologic Failure to Dolutegravir Maintenance Monotherapy

Abstract: NCT02401828.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…This finding suggests that the development of this specific resistance pathway is not sufficient by itself to predict treatment failure. As described earlier (reviewed in reference 16), other host and viral factors may contribute to these different outcomes, including immunological factors (such as the strength of the antiviral immune responses) and also the reservoir size, given that this parameter was recently reported to correlate with virological failure in people using dolutegravir monotherapy as maintenance (13). These G140A and Q148K mutations were not unexpected, considering that HIV-1 mutants with changes at integrase positions 140 and 148 were recently described to emerge in an HIV-infected humanized mouse that was treated with DTG and led to a partial viral rebound (41).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This finding suggests that the development of this specific resistance pathway is not sufficient by itself to predict treatment failure. As described earlier (reviewed in reference 16), other host and viral factors may contribute to these different outcomes, including immunological factors (such as the strength of the antiviral immune responses) and also the reservoir size, given that this parameter was recently reported to correlate with virological failure in people using dolutegravir monotherapy as maintenance (13). These G140A and Q148K mutations were not unexpected, considering that HIV-1 mutants with changes at integrase positions 140 and 148 were recently described to emerge in an HIV-infected humanized mouse that was treated with DTG and led to a partial viral rebound (41).…”
Section: Discussionmentioning
confidence: 92%
“…G118R and R263K were both identified during preclinical in vitro selection experiments with HIV under DTG pressure and later found in patients failing DTG-based ART (6,(31)(32)(33). Notably, both G118R and R263K were found to emerge from HIV sequences in the context of dolutegravir monotherapy (6,13). We previously showed that introducing G118R in SIVmac239 integrase caused an 80% decrease in enzymatic efficiency (22,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sequencing of 2-LTR circles, which form at low frequency in the cell nucleus via DNA ligation and thus provide a snapshot of viral DNA end sequences, failed to identify the hypothesized PPT extension (148). PPT mutations have been recorded in one patient who received DTG monotherapy (149), indicating that such changes may very well be clinically relevant. Additional work is required to more fully document the frequency of PPT changes in patients that fail DTG therapy as well as how such changes engender drug resistance.…”
Section: Mechanisms Of Hiv Resistance To Instismentioning
confidence: 99%
“…Despite relatively high barriers, second-generation INSTIs do select for resistance (149,159,163). As exemplified by the clinical successes of the NRTIs and NNRTIs, it would accordingly be highly beneficial to have additional drug classes that inhibit IN activity through novel mechanisms of action.…”
Section: Allinismentioning
confidence: 99%